CRISPR/Cas9 for development of disease resistance in plants: recent progress, limitations and future prospects - Ahmad, Shakeel; Wei, Xiangjin; Sheng, Zhonghua; Hu, Peisong; Tang, Shaoqing (Oxford University Press, 2020)
Several plant pathogens severely affect crop yield and quality, thereby threatening global food security. In order to cope with this challenge, genetic improvement of plant disease resistance is required for sustainable agricultural production, for which conventional breeding is unlikely to do enough. Luckily, genome editing systems that particularly clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (CRISPR/Cas9) has revolutionized crop improvement by enabling robust and precise targeted genome modifications. It paves the way towards new methods for genetic improvement of plant disease resistance and accelerates resistance breeding. In this review, the challenges, limitations and prospects for conventional breeding and the applications of CRISPR/Cas9 system for the development of transgene-free disease-resistant crops are discussed.